Understanding Corporate Criminal Liability from a Global Perspective: Whose Liability is It, After All? - Sharma, Arpita; Kumari, Puja (Kathmandu School of Law Review, 2013)
The jurisprudential foundations of the Criminal Liability of Corporations were laid down much lately in countries like France and India as compared to USA and United Kingdom. This article is a modest attempt on the part of the authors to revisit the subject matter of corporate criminal liability which is often dealt within legal literature as just another offence under the Indian Criminal Justice System. It thoroughly tracks the legislative developments since the origination of the concept in the Romanic Law in 12th-14th century till date, along with the provisions laid down and emergence of the concept in different part of the world. Judicial moods in interpretations to provisions pertaining to corporate criminal liability have been unearthed to show a conservative judiciary giving way to a liberal one, loosening the shackles of power. Laws on the corporate criminal liability need major changes- from amendments in laws to changes in judicial interpretations to changes in victim treatment and approach. This paper attempts to expound the complete subject matter in a thought-through manner to reawaken thinking of an improvised and transformed system of law. A steep rise in the number of crimes committed by the corporations clearly reveals a prima facie malfunctioning of corporate governance which, in return, calls for a much more efficient enforcement of law.